1993
DOI: 10.1111/j.1469-8137.1993.tb03880.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant response to irrigation with water enriched with carbon dioxide

Abstract: SUMMARY The influence of irrigation with CO2‐enriched water on plant development and yield is reviewed. The reason for irrigation with CO2‐enriched water was – in most cases – to increase yield. The present evaluation considers results from over a hundred studies performed since the first experiment in 1866. Special emphasis is given to the comparison of 85 experiments made by Mitscherlich in 1910 with 358 irrigation experiments made in the last 80 years. In a statistical analysis of these experiments, the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 55 publications
0
20
0
1
Order By: Relevance
“…Aeration of the nutrient solution with elevated levels of CO2 was achieved by mixing CO2-free air with pure CO2, The CO2 concentration was continuously monitored with an APPA-3 infrared gas analyzer (Anarad Inc, Santa Barbara, CA, USA), C02-free air was generated by passing air through a 1 x 0,05 m column of soda lime tested for efficacy at the beginning and the end of the experiment with the infrared gas analyser. To prevent release of CO2 from the rhizosphere and its assimilation by photosynthesis (Enoch and Olesen 1993), a fan was used to maintain a gentle air movement over the plant shoots. The air composition was routinely sampled above the lids of the containers with an ADC LCA2 infrared gas analyser (Analytical Development Corporation, Hoddesdoti, UK) and did not differ from ambient CO, concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Aeration of the nutrient solution with elevated levels of CO2 was achieved by mixing CO2-free air with pure CO2, The CO2 concentration was continuously monitored with an APPA-3 infrared gas analyzer (Anarad Inc, Santa Barbara, CA, USA), C02-free air was generated by passing air through a 1 x 0,05 m column of soda lime tested for efficacy at the beginning and the end of the experiment with the infrared gas analyser. To prevent release of CO2 from the rhizosphere and its assimilation by photosynthesis (Enoch and Olesen 1993), a fan was used to maintain a gentle air movement over the plant shoots. The air composition was routinely sampled above the lids of the containers with an ADC LCA2 infrared gas analyser (Analytical Development Corporation, Hoddesdoti, UK) and did not differ from ambient CO, concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, 13 C and 14 C tracer experiments (Amiro and Ewing 1992;Ford et al 2007 and references therein) have confirmed that DIC uptake does occur in some plants, including Phaseolus vulgaris. However, as summarized by Enoch and Olesen (1993) and Ford et al (2007), different experiments have produced sharply different estimates of the extent to which the process occurs, including cases where the effect is so small as to be unmeasurable. The only common ground in the literature seems to be a widespread agreement that the carbon contribution to fixed biomass from root uptake is at most a few percent of the input from photosynthesis, and probably much less.…”
Section: The Dead-carbon Hypothesis Root Uptake Of 14 C-depleted Dicmentioning
confidence: 99%
“…The influence of irrigation with CO 2 -enriched water on plant development and yield has been reviewed [59]. Recently, studies [38,39] showed that elevated rhizosphere dissolved inorganic carbon (DIC) under salinity stress stimulated tomato growth and was related to the site of NO 3 -reduction (root for salt-stressed plants) and higher NO 3 -uptake [41].…”
Section: Composition Of the Nutrient Solutionmentioning
confidence: 99%